Living (il)legalities in Brazil
1 online resource
Keywords: "Reflecting on some of Brazil's foremost challenges, this book considers the sometimes porous relationship between legality and illegality in a country that is undergoing significant political and societal change. It brings together work by established scholars from Brazil, Europe and the United States to think through how (il)legalities are produced and represented at the level of institutions, (daily) practice, and culture. Through a transdisciplinary approach, the chapters cover issues including informal work practices (e.g. street vendors), urban squatter movements and (il)legal building in the cities' favelas, migration, strikes and social movements traditionally demonized. Alongside social practices, the volume includes close analyses of cultural practices and cultural production, including migrant literature and indigenous art. The question of (il)legalities that this book explores resonates beyond Brazil's borders, as concepts such as 'lawfare' have crept into vocabularies, and countries the world over grapple with issues such as state interference, fake news, the definition of 'illegal' migration. This is valuable reading for scholars in Brazilian and Latin American Studies, as well as those working in anthropology, sociology, geography and political science"--